Dampak Pariwisata Terhadap Tingkat Kemiskinan di Lima Negara ASEAN: Tourism Impact on Poverty Levels in Five ASEAN Countries) - Zainuri Zainuri; Teguh Hadi Priyono; Almanda Varazizah (e-Journal Ekonomi Bisnis dan Akuntansi, 2021)
Tourism is one of the economic development strategies to reduce poverty by increasing the country's foreign exchange income in developing countries. This study aimed to analyze the impact of tourism on poverty in five ASEAN countries, namely Indonesia, Malaysia, Vietnam, the Philippines, and Thailand. The data used in this study is quantitative data with secondary data types from 2000 - 2019. The analysis method used in this research method is a panel data analysis method with the Fixed Effect Model(FEM) model. In contrast to previous research, the study examined monetary variables to use financial inclusion to determine poverty rates with coverage in five ASEAN countries. The results showed that investment variables, employment rates, and financial inclusion in the tourism sector consistently reduced poverty rates in the five ASEAN countries. In contrast, tourist consumption variables did not affect poverty rates.